Prevalence, job risk factors and coping strategies of Work Related Musculoskeletal Disorders among Physiotherapists - Prerana, Saravanan; Saravanan, Murugan; Krunal, Lad; Krishna, Ramani; Ruchi, Vadodarariya (International Journal of Occupational Safety and Health, 2016)
Background: Physiotherapists, despite having good knowledge of work related musculoskeletal disorders, are not immune to it. As literature related to these injuries in Physiotherapy profession in India is scarce, this study aims to investigate prevalence of work related musculoskeletal disorder, job risk factors commonly involved and coping strategies used among Physiotherapist in India. Methods: A semi structured questionnaire adopted from questionnaires used for similar studies around the world was circulated to 314 Physiotherapists. A total of 271 questionnaires were received back with a response rate of 86%. Mean, standard deviation, frequency, percentage and chi square test were used as appropriate for data analysis. Results: Prevalence of work related musculoskeletal disorders was found to be 62.73%. Lower back region was affected the most (65.3%) followed by neck (41.8%) and shoulder (26.5%). As per response of therapists in this study, the most common risk factors were: working in static positions for longer periods (77%), treating large number of patients in single day (68.2%) and bending and twisting back in awkward positions (65.8%).Common coping strategies adopted by respondents were: modifying positions of patient and self (54.1%), adjusting height of treatment surface (47.1%) and selection of techniques that does not aggravate or provoke discomfort (41.8%). Conclusion: This study has identified the prevalence of work related musculoskeletal disorders among Physiotherapists in India and possible risk factors associated with this profession. It has also identified the common coping strategies utilized by therapists. These findings would be significant in modifying risk factors to prevent and/or minimize work related musculoskeletal disorders among physiotherapists.